2020
DOI: 10.1007/s10212-020-00464-7
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic knowledge predicts reading and spelling skills over and above general intelligence and phonological awareness

Abstract: It is widely accepted that general intelligence and phonological awareness contribute to children's acquisition of reading and spelling skills. A further candidate in this regard is orthographic knowledge (i.e., the knowledge about permissible letter patterns). It consists of two components, word-specific (i.e., the knowledge of the spelling of specific words) and general orthographic knowledge (i.e., the knowledge about legal letter patterns of a writing system). Among German students, previous studies have s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 69 publications
12
58
4
4
Order By: Relevance
“…Since word-specific and general orthographic knowledge seem to play an important role in word-identification, it can be assumed that children with low reading proficiency use their orthographic knowledge when reading single words. Therefore, in line with previous results (e.g., Rothe et al, 2015;Zarić et al, 2020), we hypothesize that word-specific and general orthographic knowledge contribute significantly to reading at word-level, over and above the contribution of phonological awareness and naming speed in poor readers.…”
Section: The Present Studysupporting
confidence: 90%
See 4 more Smart Citations
“…Since word-specific and general orthographic knowledge seem to play an important role in word-identification, it can be assumed that children with low reading proficiency use their orthographic knowledge when reading single words. Therefore, in line with previous results (e.g., Rothe et al, 2015;Zarić et al, 2020), we hypothesize that word-specific and general orthographic knowledge contribute significantly to reading at word-level, over and above the contribution of phonological awareness and naming speed in poor readers.…”
Section: The Present Studysupporting
confidence: 90%
“…In this study, however, only one task measuring orthographic knowledge at the general level (i.e., the knowledge about frequent and infrequent double consonants) was used. Another study conducted in German by Zarić et al (2020), however, reported that word-specific and general orthographic knowledge show significant correlations with reading at word-, sentence, and textlevel. Moreover, the analyses have shown that both word-specific and general orthographic knowledge are significant predictors for reading at word-level, as well as at sentence-and text-level in German 3 rd graders without reading difficulties.…”
Section: Orthographic Knowledgementioning
confidence: 89%
See 3 more Smart Citations